2012
DOI: 10.4102/jsava.v83i1.204
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic ulcerative syndrome: Exotic fish disease threatens Africa’s aquatic ecosystems

Abstract: In late 2006 an unusual ulcerative condition in wild fish was reported for the first time in Africa from the Chobe and upper Zambezi Rivers in Botswana and Namibia. Concern increased with subsistence fishermen reporting large numbers of ulcerated fish in their catches. In April 2007 the condition was confirmed as an outbreak of epizootic ulcerative syndrome (EUS). The causative agent, Aphanomyces invadans, is a pathogenic water mould of fish that shows little host specificity. Ulcers follow infection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 13 publications
8
39
0
Order By: Relevance
“…Aquatic fungi and water molds from freshwater sources have been reported to be responsible for the infection of aquatic species [20,21,22,23,24,25]. The presence of toxic aquatic fungi in water tends to infect aquatic animals, including those that are consumed by humans.…”
Section: The Effect Of Aquatic Fungi In Seafood Consumed By Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic fungi and water molds from freshwater sources have been reported to be responsible for the infection of aquatic species [20,21,22,23,24,25]. The presence of toxic aquatic fungi in water tends to infect aquatic animals, including those that are consumed by humans.…”
Section: The Effect Of Aquatic Fungi In Seafood Consumed By Humansmentioning
confidence: 99%
“…Various fish species have been reported to have the disease called epizootic ulcerative syndrome (EUS), which is one of the most dangerous diseases in aquatic ecosystems on the African continent. This disease is caused by the water mold Aphanomyces invadans [21]. Among the highest number of infected fish are found in African aquatic systems, and some of the fish species are of economic importance [31].…”
Section: The Effect Of Aquatic Fungi In Seafood Consumed By Humansmentioning
confidence: 99%
“…His most recent contribution to diseases of freshwater fish was confirmation of the presence of Epizootic Ulcerative Syndrome (EUS) in Lake Liambezi (McHugh et al 2014). This disease was first reported by Andrew et al (2008) from the Chobe and Zambezi rivers and confirmed by Huchzermeyer and van der Waal (2008), who also described the international distribution of this disease. The disease probably originated in the Zambezi and was transmitted to the Okavango when the high flood after 2010 connected the Okavango and the Zambezi systems via the Selinda Spillway to the Linyanti Swamps.…”
Section: Aquatic Parasitology At the University Of The Free State 198mentioning
confidence: 85%
“…In sub-Saharan Africa the first report of A. invadans and an associated EUS outbreak was from Botswana in 2007, followed by Zambia in 2008 (Andrew et al 2008). Subsequently 27 fish species from the region have been shown to be susceptible to EUS (FAO 2009;Choongo et al 2009;Songe et al 2012;Huchzermeyer & Van der Waal 2012). Lesions, suspected to be associated with EUS have previously been reported from Lake Liambezi by Van der Waal (2008;.…”
mentioning
confidence: 87%